Chemical chronobiology: Toward drugs manipulating time. Issue 14 (7th May 2015) - Wallach, Thomas; Kramer, Achim
Abstract : Circadian clocks are endogenous timing systems orchestrating the daily regulation of a huge variety of physiological, metabolic and behavioral processes. These clocks are important for health – in mammals, their disruption leads to a diverse number of pathologies. While genetic and biochemical approaches largely uncovered the molecular bases of circadian rhythm generation, chemical biology strategies targeting the circadian oscillator by small chemical compounds are increasingly developed. Here, we review the recent progress in the identification of small molecules modulating circadian rhythms. We focus on high‐throughput screening approaches using circadian bioluminescence reporter cell lines as well as describe alternative mechanistic screens. Furthermore, we discuss the potential for chemical optimization of small molecule ligands with regard to the recent progress in structural chronobiology.